Immunogenicity assessment strategy for a chemically modified therapeutic protein in clinical development - Hagman, Charlotte; Chasseigne, Gaetan; Nelson, Robert; Anlauff, Florian; Kagan, Mark; Goldfine, Allison B.; Terszowski, Grzegorz; Jadhav, Maria (Frontiers in Immunology, 2024)
The clinical immunogenicity assessment for complex multidomain biological drugs is challenging due to multiple factors that must be taken into consideration. Here, we describe a strategy to overcome multiple bioanalytical challenges in order to assess anti-drug antibodies (ADA) for a novel and unique chemically modified protein therapeutic. A risk-centered approach was adopted to evaluate the immunogenic response to a modified version of human growth differentiation factor 15 (GDF15) connected to an albumin-binding fatty acid via a polyethylene glycol (PEG) linker. Key steps include monitoring anti-drug antibodies (ADAs), using a standard tiered approach of screening and confirmation. To deepen our understanding of ADA response, as a third tier of immunogenicity assessment, novel extensive characterization using a set of assays was developed, validated, and used routinely in clinical sample analysis. This characterization step included performance of titration, mapping of ADA response including anti-GDF15 and anti-PEG–fatty-acid antibody characterization, and assessment of the neutralizing anti-drug antibodies (NAbs) using cell-based assays for immunogenicity in parallel. The analytical methods were applied during two clinical trials involving both healthy volunteers and overweight or obese patients. We observed low incident rates for ADA and no ADAs against the PEG linker with fatty acid conjugation. In one of the clinical studies, we identified neutralizing ADAs. The proposed novel strategy of extensive characterization proved effective for monitoring the presence of ADAs and NAbs and can be used to support clinical development of a broad range of chemically modified proteins and multidomain biotherapeutics.